Catalysts and Challenges in Essay Writing Proficiency among College Students: Insights from Motivation, Literacy, Cognition, and Language Skills - Anaktototy, Karolis -; Monica, Monica; Patty, Jusak (Makassar State University, 2024)
Abstract. This study delves into the various factors that influence the essay writing skills of college students, including motivation, literacy, cognitive abilities, and language proficiency. A mixed-method approach was used, combining qualitative and quantitative methods. The data was collected through questionnaire surveys and interviews to analyze the impact of these factors on students' writing capabilities. The findings reveal that the majority of students find writing enjoyable, with over 90% expressing interest in essay composition. However, procrastination tendencies were observed, with 46% of students admitting to submitting essays on the last day. Furthermore, excessive instructor feedback negatively affected the motivation of more than 50% of respondents. Regarding literacy, approximately 66% of students engage in daily reading, a critical component for enhancing writing skills. A strong correlation between reading and writing was identified, as students often utilize relevant sources to support their essays. However, 75% of participants admitted to reading primarily within the confines of coursework. Cognitive capabilities played a significant role, with over 80% of students effectively planning and developing essay content. However, content comprehension proved to be challenging for 56%, affecting the coherence of their essays. Interviews revealed difficulties in paragraph development and topic selection. Language skills were deemed essential for coherent writing, with 80% of students constructing sentences adeptly and employing grammar effectively. Despite these skills, students struggled with syntax and word choice. Interviews highlighted issues with sentence construction and word selection, impacting the clarity of their messages. The research findings can potentially be implemented to design strategies, models, and learning media that focus on improving the essay writing proficiency of college students.Keywords: Motivation, Literacy, Cognitive Abilities, Language Skills, Essay Writing